Bioactive Silvadur loaded polyacrylonitrile nanofibrous membranes for wound dressing applications. (1st November 2022) - Ayaz, Maira; Salam, Abdul; Khan, Saif Ullah; Khan, Muhammad Qamar; Hussain, Tanveer; Kim, Ick Soo
Abstract: Persistent wounds are the most problematic for the patient as well as for the health system. Skin wounds are most exposed to bacterial attacks, which not only cause wound infections but also slow down the healing process. There is a dire need to develop a better wound dressing or scaffold material that can increase the wound healing process. This study involves the development of electrospun nanofibers based on Silvadur-loaded polyacrylonitrile membranes. Samples were developed by using five different concentrations (2 wt%, 4 wt%, 6 wt%, 8 wt%, and 10 wt%) of Silvadur loaded in PAN solution. Resultant nanofibers were characterized by SEM, FTIR, XRD, and antibacterial tests. SEM analysis confirms that all the prepared electrospun nanofibrous membranes have smooth and beads-free surfaces. The average diameter of developed nanofibers lies in the range of 150 nm to 190 nm. It was confirmed that as the concentration of Silvadur increased the diameter of nanofibers also increased due to the increase in the viscosity of the electrospinning solution. FTIR interpretation confirms that the interaction between the PAN and Silvadur is physical, not chemical. XRD analysis reflects the crystallographic and macromolecular structure of prepared electrospun nanofibers. A qualitative antibacterial test was performed to check the antibacterial properties of prepared electrospun nanofibers against gram-negative bacteria ( Escherichia Coli ) and gram-positive bacteria ( Staphylococcus Aureus ). The result reveals that nanofibers loaded with the maximum concentration of Silvadur show the maximum antibacterial activity of 92.25% against Escherichia Coli and 98.52% against Staphylococcus Aureus . The higher antibacterial activity against gram-negative bacteria is due to the thinner cell wall as compared to the gram-positive bacteria.